Cardiometabolic Morbidity and Other Prognostic Factors for Mortality in Adult Hospitalized COVID-19 Patients in North Jakarta, Indonesia - Arvin Pramudita; Siti Rosidah; Novi Yudia; Jeffri Simatupang; Wulan Pingkan Sigit; Rita Novariani; Priscilia Myriarda; Bambang Budi Siswanto (Ubiquity Press, 2022)
Background: Although there have been several studies investigating prognostic factors for mortality in COVID-19, there have been lack of studies in low- and middle-income countries, including Indonesia. To date, the country has the highest mortality rate among Asian countries. Objective: We sought to identify the prognostic factors of mortality in hospitalized patients with COVID-19 in Jakarta. Methods: In this retrospective cohort study, we included all adult inpatients (≥18 years old) with confirmed COVID-19 from Koja General Hospital (North Jakarta, Indonesia) who had been hospitalized between March 20th and July 31st, 2020. Demographic, clinical, laboratory, and radiology data were extracted from the medical records and compared between survivors and non-survivors. Univariate and multivariate logistic regression analysis were used to explore the prognostic factors associated with in-hospital death. Results: Two hundred forty-three patients were included in the study, of whom 32 died. Comorbid of hypertension (OR 3.59; 95% CI 1.12-11.48; p = 0.031), obesity (OR 6.34; 95% CI 1.68-23.98; p = 0.007), immediate need of HFNC and/or IMV (OR 64.93; 95% CI 11.08-380.61; p < 0.001), abnormal RDW (OR 3.68; 95% CI 1.09-12.34; p = 0.035), ALC < 1,000/µL (OR 3.51; 95% CI 1.08-11.44; p = 0.038), D-dimer > 500 ng/mL (OR 9.36; 95% CI 1.53-57.12; p = 0.015) on admission, as well as chloroquine treatment (OR 3.61; 95% CI 1.09-11.99; p = 0.036) were associated with greater risk of overall mortality in COVID-19 patients. The likelihood of mortality increased with increasing number of prognostic factors. Conclusion: The potential prognostic factors of hypertension, obesity, immediate need of HFNC and/or IMV, abnormal RDW, ALC < 1,000/µL, D-dimer > 500 ng/mL, and chloroquine treatment could help clinicians to identify COVID-19 patients with poor prognosis at an early stage.